Zirconia sintered compact and production method thereof
By applying an alternating current electric field to zirconia samples within controlled parameters, the method shortens sintering time and reduces thermal and environmental impact while producing high-density, homogeneous zirconia sintered bodies.
Patent Information
- Application Number
- JP2023095008
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-08
- Publication Date
- 2024-12-19
AI Technical Summary
Conventional flash sintering methods for producing high-density zirconia sintered bodies require prolonged energization times, leading to increased environmental and thermal loads, and the temperature control is often based on furnace temperature rather than the actual sample temperature.
A method involving heating a zirconia sample in a sintering furnace to a predetermined temperature, followed by applying an alternating current electric field to promote sintering through the flash phenomenon, with specific conditions including a stabilizing element concentration, effective temperature range, and controlled electric field parameters to achieve densification in less than 5 minutes.
This approach reduces sintering time, minimizes environmental impact, and achieves a high-density, homogeneous zirconia sintered body of superior quality by controlling the process at the actual sample temperature, thereby reducing thermal load.
Smart Images

Figure 2024176463000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a zirconia sintered body and a manufacturing method thereof, and more specifically, to a technique for manufacturing a high-density, homogeneous zirconia sintered body while reducing the environmental load and reducing the thermal load on a target sample during sintering. [Background technology]
[0002] Flash sintering is a sintering method that utilizes the phenomenon (so-called flash phenomenon) in which a sudden increase in current value and temperature occurs at a certain temperature when an electric field is applied to a molded object to be sintered, and is a sintering method that was announced by Raj et al.'s research group in 2010 (see Non-Patent Document 1). In the first report by Raj et al., 3 mol% Y2O3 stabilized tetragonal ZrO2 (3Y-TZP) was the subject, and it was reported that when a direct current electric field of 120 V / cm was applied, for example, densification began at a low temperature of 850°C in an air-pressure-free environment, and a densified sintered body with a relative density of 95% or more was obtained in a short sintering time of only 5 seconds. Considering that a general sintering method requires a high temperature of 1400°C to 1500°C and several hours of sintering for 3Y-TZP, it can be seen that flash sintering can achieve sintering densification at a low temperature and in a short time. Due to these characteristics, flash sintering is attracting attention as a sintering method that is a new energy-saving process for ceramics. For zirconia as well, a method for producing a zirconia sintered body with high relative density by flash sintering has been proposed.
[0003] For example, Patent Document 1 proposes a technique using flash sintering to improve the density of a sintered body, and reports that this technique has produced a zirconia sintered body with a stable fine structure in which yttrium (Y) is distributed relatively uniformly in cubic zirconia (ZrO2) or tetragonal ZrO2. Specifically, it has been reported that densification of zirconia is promoted by heating a compact (pressed powder) to a temperature higher than the temperature at which the flash phenomenon occurs and then applying an electric field. After heating to 1200°C, which is relatively lower than the conventional sintering temperature, the sintered body was sintered at an applied voltage of 60 V / cm and a limited current of 700 mA / mm. 2 It has been reported that by applying an electric field with a frequency of 100 Hz and maintaining it for 5 minutes after the limiting current is reached, a zirconia sintered body with very few voids and a relative density of over 99% can be obtained.
[0004] In addition, Patent Document 2 proposes a method for producing a zirconia sintered body that has a higher sintered body density than conventional flash sintering that applies a high applied voltage, by flash sintering using a low applied voltage. This method for producing a zirconia sintered body includes a current increasing step in which the current flowing through the molded body is increased while controlling the current value flowing through the molded body so that the shrinkage rate of the molded body is constant, and a densification step in which the molded body is densified by holding the molded body at a temperature where the flash phenomenon can occur and under a condition in which the current flowing through the molded body shows the current value of the densification current after the current increasing step. Specifically, the molded body is heated to 1020°C, and while maintaining this temperature, the current is increased while adjusting the increase in the current flow while finely setting the limiting current value so that the shrinkage rate of the molded body is constant, and the current is increased from the current value of the starting current to the current value of the densification current over 16 minutes, and the molded body is held for 5 minutes while maintaining the temperature at 1020°C to densify the molded body. As a result, it has been reported that a zirconia sintered body with a relative density of 99% or more was obtained. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2019-182689 A [Patent Document 2] Patent Publication No. 2022-105852 [Non-patent literature]
[0006] [Non-Patent Document 1] Rapid Communications of the American Ceramic Society, Vol.93, No.11, (2010) p.3556-3559 Summary of the Invention [Problem to be solved by the invention]
[0007] In the above-mentioned Patent Document 1, in which a high-density zirconia sintered body is said to have been obtained by the flash sintering method, the time for passing current through the molded body to be sintered is 5 minutes. In Patent Document 2, the holding time at 1020°C is 5 minutes, but since the current is passed for 16 minutes in the current increasing step, the time for passing current through the molded body to be sintered is 21 minutes. Furthermore, if the time for passing current during the temperature increasing step is added, the total time for passing current exceeds 21 minutes.
[0008] Thus, in the conventional method, the time for passing current through the green body to be sintered is 5 minutes or more. However, from the viewpoints of reducing the environmental load and the thermal load on the target sample during sintering, it is desirable to obtain a high-density, homogeneous zirconia sintered body with a shorter current passing time.
[0009] In addition, in the conventional flash sintering method, the temperature at which the green body is flash sintered is managed and controlled by the furnace temperature. For example, Patent Document 2 states that "the green body temperature can be obtained by measuring the temperature in the device in which the green body is heated," and the furnace temperature is considered to be the temperature of the green body during sintering. However, the temperature detected by a measuring means such as the thermocouple of a differential dilatometer is only the temperature in the furnace, and not the temperature of the green body in the sintering process. The parameter that is essentially important in the sintering of a green body is not the furnace temperature, but the actual sample temperature (effective temperature) of the green body in which densification is progressing due to the flash phenomenon.
[0010] Based on the above viewpoints, the present disclosure aims to produce a high-density, homogeneous zirconia sintered body while reducing the environmental load and the load on the sintered body by enabling sintering in a short time compared to the conventional flash sintering method. It also aims to improve the quality of a high-density, homogeneous zirconia sintered body by performing sintering at the actual sample temperature (effective temperature) of the sample to be sintered, in which densification is progressing due to the flash phenomenon. [Means for solving the problem]
[0011] In order to solve the above-mentioned problems, the contents of the present invention are as described in the claims, and the gist of the present disclosure is as follows. (1) A process for heating a zirconia sample to be sintered in a sintering furnace, the process being carried out at a furnace temperature (T f The method includes a heating step of heating the zirconia sample to a predetermined temperature, and a densification step of applying an AC electric field to the zirconia sample to be sintered to promote sintering and densification of the sample by a flash phenomenon, the zirconia sample to be sintered containing a stabilizing element at a concentration of 2.0 mass % or more and less than 5.2 mass % in terms of oxide, and the densification step is performed at an effective temperature (T s ) is in the range of 900°C or more and 1650°C or less. T s =[(T f+273.15) 4 +W / εAσ] 0.25 -273.15 T s and T f Unit:℃ W: Input power (mW) = Applied current (mA) x Applied voltage (V) ε: Emissivity of the sample to be sintered, where ε=1 σ: Stephan-Boltzmann constant (5.67×10 -8 Wm -2 K -4 ) A: Surface area of the sample to be sintered where the AC electric field is applied (mm 2 ) (2) The method for producing a zirconia sintered body according to (1), wherein the predetermined furnace temperature in the heating step is 600°C or higher and 1200°C or lower. (3) The method for producing a zirconia sintered body according to (1) or (2), wherein the application time of the AC electric field in the densification step is less than 5 minutes. (4) The method for producing a zirconia sintered body according to any one of (1) to (3), wherein the frequency of the AC electric field is higher than 10 Hz and not higher than 2000 Hz. (5) When the AC electric field is applied, the current density is 0 mA / mm 2 Higher than 100mA / mm 2 The method for producing a zirconia sintered body according to any one of (1) to (4), which is as follows: (6) The method for producing a zirconia sintered body according to any one of (1) to (5), wherein the electric field strength when the AC electric field is applied is higher than 0 V / cm and not more than 200 V / cm. (7) The method for producing a zirconia sintered body according to any one of (1) to (6), wherein the stabilizing element is at least one selected from the group consisting of Y, Ca, Mg and lanthanoids. (8) The method for producing a zirconia sintered body according to any one of (1) to (7), wherein the zirconia sample to be sintered contains alumina. (9) The method for producing a zirconia sintered body according to (8), wherein the alumina content is more than 0 mass% and 1 mass% or less. (10) A zirconia sintered body containing a stabilizing element, the concentration of the stabilizing element in the zirconia sintered body being 2.0 mass% or more and less than 5.2 mass% in terms of oxide, and when the grain size of the sintered body is evaluated in terms of a circle equivalent diameter, the average crystal grain size (d s ) and the average crystal grain size (d i ) and the particle size difference (d i -d s ) is less than 40 nm. (11) The zirconia sintered body according to (10), having a relative density of 98% or more as calculated by the following formula: Relative density (%): (measured density ρ / true density ρ0) x 100 Measured density ρ: The ratio of mass measured by mass measurement to volume measured by Archimedes' method (g / cm 3 ) True density ρ0: The value calculated by the following formula when the content (mol%) of the oxide of the stabilizing element contained in the sintered body is X ρ0=[124.25(100-X)+225.81X] / 2αβ[150.5(100+X)] Here, α and β have the following values: α=0.5080+0.06980X / (100+X) β=0.5195-0.06180X / (100+X) (12) The zirconia sintered body according to (10) or (11), wherein the stabilizing element is at least one selected from the group consisting of Y, Ca, Mg and lanthanoids. Effect of the Invention
[0012] The present disclosure makes it possible to produce a high-density, homogeneous zirconia sintered body while shortening the sintering time compared to the conventional flash sintering method, reducing the environmental load, and reducing the thermal load on the target sample during sintering. In addition, since sintering is performed at the actual temperature (effective temperature) of the sintered sample in which densification is progressing due to the flash phenomenon, the high-density, homogeneous zirconia sintered body can be produced with high quality. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a diagram illustrating an example of the shape of a sample to be flash sintered. [Diagram 2] FIG. 2 is a diagram showing an example of a state in which a conducting wire (Pt wire) is directly connected to a sample to be sintered in order to apply an AC electric field to the sample. [Diagram 3] FIG. 3 is a diagram showing an example of a state in which Pt paste is applied near the end of a sample to be sintered and then a conductor (Pt wire) is connected to the Pt paste application portion in order to apply an AC electric field to the sample to be sintered. [Figure 4] FIG. 4 is a diagram for explaining an outline of the structure of a manufacturing apparatus for a zirconia sintered body used in the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, the method for producing a zirconia sintered body according to the present disclosure and the zirconia sintered body obtained by the method will be described with reference to the drawings, but the following description is merely an example of an embodiment of the present disclosure, and the present invention is not limited to the contents of the description. The meanings of the terms used in this specification are as follows.
[0015] The "flash phenomenon" is a phenomenon in which the current value rises suddenly when a voltage is applied to a sample to be sintered. This sudden rise in the current value also causes the temperature of the sample to rise. "Flash sintering" is a sintering method that densifies the sample to be sintered by using the flash phenomenon. The "flash temperature" is the temperature at which the flash phenomenon occurs, and is the temperature at which the current value rises (increases) suddenly when the temperature is raised while a voltage is applied.
[0016] The "AC electric field" refers to the electric field applied to the sample to be sintered when an AC power source and the sample to be sintered are connected with a conductor and a current is passed through the sample, and is the applied voltage (V) divided by the distance between the electrodes of the sample to be sintered (cm) (V / cm). This "AC electric field" is sometimes written as "AC electric field" or "electric field strength". The AC waveform is arbitrary, but it is desirable to use a square wave, a sine wave, a triangular wave, or a sawtooth wave, and a square wave or a sine wave is preferable. The frequency of the AC electric field is preferably in the range of more than 10 Hz and less than 2000 Hz, and more preferably in the range of more than 100 Hz and less than 1000 Hz.
[0017] The "applied current" is the current that flows when an electric field is applied to the sample to be sintered, and the value is the applied current value (mA). The "current density" is the current value that flows per unit area of the sample to be sintered, and is expressed as the applied current value (mA) per unit cross-sectional area (mm 2 ) divided by (mA / mm 2 ).
[0018] FIG. 1 is a diagram illustrating an example of the shape of a sample to be flash sintered. The sample to be sintered 10 has a rectangular parallelepiped shape as shown in this figure, and a current (I AC ) flows, the cross-sectional area S (mm 2 ) is a(mm) × b(mm), so the current density (mA / mm 2 ) is the applied current value (mA) / cross-sectional area S (mm 2 ) can be calculated.
[0019] The "limited current value" is the current value of the energizing current (limited current) that is set as the upper limit of the current value flowing through the sample to be sintered, and is intended to control the current flowing through the sample to not exceed this current value. The "limited current density" is the current density of the limited current.
[0020] The "electrode distance" of the sample to be sintered is the distance across which an electric field is applied within the sample to be sintered.
[0021] 2 and 3 are diagrams showing examples of a state in which a conductor is connected to apply an AC electric field to a sample to be sintered. In the embodiment shown in FIG. 2, the conductor (Pt wire: 20) is directly connected to the sample to be sintered 10. On the other hand, in the embodiment shown in FIG. 3, in order to reduce the contact resistance between the sample to be sintered 10 and the conductor 20, Pt paste 30 is applied near the end of the sample to be sintered 10, and then the conductor (Pt wire) 20 is connected to this Pt paste application part 30. The "distance between electrodes" in the embodiment shown in FIG. 2 is the shortest distance between the conductors (Pt wires) (20a and 20b), L ew In the case of the embodiment shown in FIG. 3, the "electrode distance" is the shortest distance between the Pt paste application parts (30a and 30b), L ep It is.
[0022] "Current application time" refers to the total time (min) that an AC electric field was applied to the sample to be sintered.
[0023] The "effective temperature" is the temperature of the sample to be sintered where densification is progressing due to the flash phenomenon, and in this disclosure, this temperature is considered to be the actual temperature of the sample to be sintered. When an AC electric field is applied to the sample to be sintered, in addition to the amount of heat from the external heating by the heater of the sintering furnace, heat generation due to Joule heat of the sample itself and heat loss due to radiation occur. As a result of investigation, the inventors of the present invention believe that in a steady state, the heat generation due to Joule heat of the sample to be sintered and the heat loss due to radiation are equal, and they conclude that when the temperature inside the sintering furnace is T f (℃) at "effective temperature (T s )" (℃) is calculated using the following formula. T s =[(T f +273.15) 4+W / εAσ] 0.25 -273.15 W: Input power (mW) = Applied current (mA) x Applied voltage (V) ε: Emissivity of the sample to be sintered, where ε=1 σ: Stephan-Boltzmann constant (5.67×10 -8 Wm -2 K -4 ) A: Surface area of the sample to be sintered where the AC electric field is applied (mm 2 )
[0024] The furnace temperature T f In determining the temperature (°C), the temperature inside the furnace is determined by, for example, a temperature detected by a thermocouple of a differential thermal dilatometer and displayed on a display as the electric furnace temperature, as in the case of a commonly used temperature monitor for an electric furnace. As described later, in the present disclosure, it is preferable to carry out the densification step under conditions in which the effective temperature (Ts) of the sample to be sintered is in the range of 900°C or higher and 1650°C or lower.
[0025] In addition, the surface area A (mm 2 ) is, for example, A = 2(a + b) × L in the embodiment shown in FIG. ew In the embodiment shown in FIG. 3, A=2(a+b)×L ep It becomes.
[0026] The term "green body" refers to a compact made of powder in which powder particles are aggregated by physical forces to maintain a certain shape. The green body may contain a binder. In this specification, the term "green body" may be used in a broad sense, including "preliminary sintered body."
[0027] Hereinafter, the method for producing a zirconia sintered body according to the present disclosure will be described with reference to an example of an embodiment. As will be apparent from the following description, the method for producing a zirconia sintered body according to the present embodiment is a process of heating a zirconia molded body, which is a sample to be sintered, in a sintering furnace, and the furnace temperature (T f) to a predetermined temperature, and a densification step in which, after the heating step, an AC electric field is applied to the zirconia molded body to promote sintering and densification of the molded body by a flash phenomenon. The zirconia molded body contains a stabilizing element at a concentration of 2.0 mass % or more and less than 5.2 mass % in terms of oxide. The densification step is performed at an effective temperature (T s ) is carried out under conditions in the range of 900°C or more and 1650°C or less.
[0028] In the manufacturing method of this embodiment, the concentration of the stabilizing element contained in the zirconia molded body is 2.0 mass% or more and less than 5.2 mass% in terms of oxide. This stabilizing element content concentration is lower than that of the conventional method. According to the present disclosure, the thermal load on the target sample during sintering is reduced, so that a dense, homogeneous, high-quality zirconia sintered body can be obtained even if the zirconia molded body contains a stabilizing element at a relatively low concentration. In addition, a dense and homogeneous zirconia sintered body can be obtained in a shorter time than the conventional sintering method, thereby reducing the environmental load.
[0029] <Zirconia molding> The zirconia molded body to be the sintered sample in the present disclosure is obtained by molding zirconia powder. There is no particular limitation on the method for producing the zirconia powder to be molded, but a preferred method is a hydrolysis method. The zirconia powder contains a stabilizing element as an oxide, and the zirconia powder is compressed to form a molded body. The above-mentioned zirconia powder is preferably partially stabilized zirconia. Examples of the stabilizing element include Y, Ca, Mg, and lanthanoids, and at least one selected from these element groups can be contained. Examples of such partially stabilized zirconia include partially stabilized zirconia containing yttria. In addition, such zirconia powder may contain alumina. In that case, it is preferable to mix the sintered body so that the content of alumina in the sintered body is more than 0 mass% and 1 mass% or less.
[0030] There is no particular limitation on the shape and size of the molded body. The shape of the molded body may be any shape depending on the application, such as a disk, a cylinder, a cube, a rectangular parallelepiped, a polygonal shape, a nearly polygonal shape, a sphere, or a nearly spherical shape. The size of the molded body may be a size to which a voltage can be uniformly applied. For example, a rectangular molded body having a length of 5 mm, a width of 5 mm, and a length of 30 mm can be exemplified. The molded body to be sintered may be a large molded body prepared in advance and processed to a molded body of an appropriate size.
[0031] There are no particular limitations on the molding conditions, and any conditions may be used. When molding by cold isostatic pressing (CIP), examples of conditions include a primary pressure of 9.8 MPa or more and 196 MPa or less, and a CIP pressure of 98 MPa or more and 294 MPa or less.
[0032] The above-mentioned molded body may be pre-sintered prior to flash sintering. Examples of the conditions for pre-sintering include a temperature rise rate of 10°C / h to 300°C / h, a holding temperature range of 500°C to 1200°C, a pre-sintering holding time of 0.1 hours to less than 2.0 hours, and a temperature drop rate of 10°C / h to less than 500°C / h.
[0033] Next, each step in the method for producing a zirconia sintered body according to the present disclosure will be described.
[0034] <Manufacturing equipment> 4 is a block diagram for explaining the outline of the structure of the manufacturing apparatus 100 for zirconia sintered bodies used in the present disclosure. In the example shown in this figure, a sample 10 to be sintered, connected with a conductor (Pt wire: 20), is set in a sintering furnace 40, and an AC electric field is applied to the sample 10 to be sintered via a power supply device 50. The sintering furnace 40 is for raising the temperature during sintering of the sample 10 to be sintered, and is, for example, an electric furnace. In the example shown in this figure, a thermocouple 60 is provided to monitor the temperature inside the sintering furnace 40.
[0035] This device 100 is configured to be able to control the value of the current flowing through the molded body by setting a limiting current value and controlling the current. The current can be limited using a commercially available power supply device or the like.
[0036] <Sintering process in this embodiment> The sintering process in this embodiment includes a step of placing the zirconia molded body 10, which is the sample to be sintered, into a sintering furnace 40 while connected to a power source by a conductor 20, and then raising the temperature inside the furnace to a predetermined temperature in order to heat the zirconia molded body (heating step), and a densification step (flash sintering step) in which, after this heating step, an alternating current of a predetermined limited current value is passed through the zirconia molded body 10 (i.e., a predetermined alternating electric field is applied) to promote sintering and densification of the molded body by the flash phenomenon.
[0037] There is no particular restriction on the conductor connecting the zirconia compact, which is the sample to be sintered, and the power source, but the material of the part in contact with the compact is preferably Pt. As already exemplified, it is also preferable to apply Pt paste to the contact part between the compact and the conductor. By applying Pt paste, the electrical resistance of the contact part between the compact and the conductor when three-phase AC is applied can be reduced.
[0038] The furnace temperature reached in the above-mentioned heating process (T f ) may be a temperature (flash temperature) at which the zirconia molded body causes a flash phenomenon. The flash temperature depends on the applied voltage, the type of material of the ceramic molded body, etc., and generally, the higher the applied voltage, the lower the flash temperature can be. In the present disclosure, the ceramic molded body is a zirconia molded body, and the furnace temperature is preferably 600°C or higher, more preferably 800°C or higher. The furnace temperature is preferably 1200°C or lower, more preferably less than 1200°C. For example, the predetermined furnace temperature in this heating step is set in the range of 600°C or higher and 1200°C or lower.
[0039] The limiting current density (current density when an AC electric field is applied) during the above-mentioned densification process (flash sintering process) is 0 mA / mm 2 Higher than 100mA / mm 2 It is preferable that the frequency of the AC electric field is higher than 10 Hz and lower than 2000 Hz, and the electric field strength during application of the AC electric field is higher than 0 V / cm and lower than 200 V / cm. Furthermore, it is preferable that the application time of the AC electric field in this densification step is less than 5 minutes, for example, 3 minutes or less. According to the present disclosure, even with such a short sintering time, a high-density, homogeneous, high-quality zirconia sintered body can be obtained.
[0040] The above-mentioned densification step may be in an embodiment including a first step (power increase step) of increasing the current density when an AC electric field is applied, and a second step (maintenance step) of maintaining the AC electric field applied state at the current density reached in the first step. In the power increase step, the rate at which the current density when an AC electric field is applied (also referred to as the "power increase rate") is increased may be controlled, and the current density may be gradually increased to the current density in the maintenance step (also referred to as the "maintenance current density"). By controlling the power increase rate as described above, it is possible to suppress power overshoot when the maintenance electric field is applied. When the power increase step is provided, there is no particular restriction on the power increase rate, but for example, a lower limit of 0.1 mA / mm 2 s, with an upper limit of 10 mA / mm 2 Even when such a conductive step is provided, the application time of the AC electric field in the densification step is preferably less than 5 minutes, for example, 3 minutes or less. In other words, the total application time in the voltage increasing step and the holding step is preferably less than 5 minutes.
[0041] The holding step is started when the current density reaches a preset holding current density (set holding current density) if no power overshoot occurs, whereas if a power overshoot occurs, the current density once exceeds the set holding current density, and then decreases to reach the set holding current density, so that the holding step is started when the set holding current density is reached.
[0042] In the present disclosure, the temperature at which the green body is flash sintered is not managed and controlled by the furnace temperature, but by the actual temperature (effective temperature) of the green body in which densification is progressing due to the flash phenomenon. As described above, the "effective temperature" is the actual temperature of the sample to be sintered in which densification is progressing due to the flash phenomenon. When an AC electric field is applied to the sample to be sintered, in addition to the amount of heat from the external heating by the heater of the sintering furnace, heat generation due to Joule heat of the sample itself and heat loss due to radiation occur. Therefore, in the present disclosure, as already explained, when the temperature inside the sintering furnace is T f (℃) at "effective temperature (T s )" (℃) is calculated using the following formula. T s =[(T f +273.15) 4 +W / εAσ] 0.25 -273.15 If the power increase rate is not controlled in the power increase step, power overshoot may occur, and the maximum effective temperature in the power increase step may be higher than the effective temperature in the holding step. Therefore, in this specification, the effective temperature in the holding step is referred to as the "sample temperature during holding" and the effective temperature in the power increase step is referred to as the "maximum sample temperature during power increase" to distinguish them.
[0043] <Zirconia sintered body> The zirconia sintered body obtained by the present disclosure is a zirconia sintered body containing a stabilizing element. Preferably, the concentration of the stabilizing element in the zirconia sintered body is 2.0 mass% or more and less than 5.2 mass% in terms of oxide. In a preferred embodiment, when the grain size of the sintered body is evaluated by the circle equivalent diameter, the average crystal grain size (d s ) and the average grain size in the inner region, which is deeper than the surface region (d i ) and the particle size difference (d i -d s ) is preferably 100 nm or less, more preferably less than 40 nm.
[0044] The average grain size in the surface region (d s ) and the average grain size in the inner region (d i ) are preferably in the range of 200 nm or more and 1000 nm or less. Here, the "average crystal grain size" is the average diameter based on the number of zirconia crystal grains constituting the sintered body, and is calculated by the planimetric method using a scanning electron microscope (SEM) observation image obtained by heat-treating a mirror-polished sintered body and then observing it. More specifically, a circle of radius r is drawn on the SEM observation image, the number of particles located within the circle and on the circumference are counted, and the average grain size D [nm] is calculated by the following formula. D = (1.77 × r) / (N A ) 0.5 N A =N1+N2 / 2 r: radius of the circle drawn on the SEM image N1: Number of particles located within the circle N2: Number of particles located on the circumference The radius of the circle drawn in the SEM observation image described above may be set so that the total number of particles located within and around the circle is 100 ± 50. SEM observation may be performed using a general scanning electron microscope (e.g., JSM-IT500LA, manufactured by JEOL Ltd.).
[0045] SEM observation may be performed by appropriately setting the observation magnification so that the number of crystal particles to be image-analyzed (crystal particles whose crystal grain boundaries are observed without interruption in the SEM observation image) is 200±50. In order to suppress variations in the observed crystal particles due to differences in the SEM observation locations, it is preferable to obtain SEM observation images so that the total number of crystal particles observed in 2 or more, preferably 3 or more and 5 or less, SEM observation images is the above-mentioned number of crystal particles. The SEM observation conditions are, for example, an acceleration voltage of 5 to 15 kV and an observation magnification of 5,000 to 40,000 times.
[0046] In addition, since it may be difficult to observe the contrast of the grain boundaries in a mirror-polished sintered body, it is preferable to perform heat treatment within a range in which the grain size does not change. For example, the conditions for such heat treatment include holding the temperature at least 50°C lower than the sintering temperature (effective temperature) for 0.1 hours or more. For example, heat treatment is performed at a heat treatment temperature in the range of 1050°C to 1540°C for 0.1 hours to 1.0 hours.
[0047] The zirconia sintered body obtained by the manufacturing method of this embodiment may have the same composition as the molded body. Such a zirconia sintered body is preferably a partially stabilized zirconia sintered body, and more preferably a partially stabilized zirconia sintered body containing yttria.
[0048] In the case of a partially stabilized zirconia sintered body containing yttria, the lower limit of the yttria content is preferably 2.0 mass%, more preferably 2.5 mass%, and the upper limit is preferably less than 5.2 mass%, more preferably less than 4.5 mass%, and even more preferably less than 3.6 mass%.
[0049] As described above, examples of the stabilizing element include Ca, Mg, and lanthanoids in addition to Y. The stabilizing element contained may be at least one element selected from this group of elements.
[0050] The relative density of the zirconia sintered body obtained by the manufacturing method of this embodiment is preferably 98% or more and 100% or less. Here, the relative density of the sintered body is calculated by the following formula. Relative density (%): (measured density ρ / true density ρ0) x 100 Measured density ρ: The ratio of mass measured by mass measurement to volume measured by Archimedes' method (g / cm 3 ) True density ρ0: The value calculated by the following formula when the content (mol%) of the oxide of the stabilizing element contained in the sintered body is X ρ0 = [124.25(100 - X) + 225.81X] / 2αβ[150.5(100 + X)] Here, α and β are the following values. α = 0.5080 + 0.06980X / (100 + X) β = 0.5195 - 0.06180X / (100 + X)
Example
[0051] Hereinafter, embodiments of the present disclosure will be described by way of examples. However, this embodiment is merely illustrative, and the present disclosure is not limited thereto.
[0052] <Relative density> The measured density of the sintered body was measured by the Archimedes method. Prior to this measurement, the mass of the dried sintered body was measured, and then the sintered body was placed in water and boiled for 1 hour as a pretreatment. The true density was calculated using the above-described mathematical formula, and the relative density (%) was determined from the value of the measured density with respect to the true density.
[0053] <SEM observation> A general scanning electron microscope (model name: S3000, manufactured by Hitachi High-Technologies Corporation) was used to obtain an SEM observation image of the fracture surface of the sample after sintering. The SEM observation was performed under the conditions of an acceleration voltage of 20 kV and an observation magnification of 10,000 times. From the obtained SEM observation image, the particle diameters of 150 ± 50 crystal particles were measured, and the average crystal grain size was determined. Prior to the SEM observation, the fracture surface of the sintered body sample was polished to a mirror surface (Ra ≤ 0.02 μm) by polishing, and then heat etching treatment was performed as a pretreatment.
[0054] <Examples 1 to 4 and Comparative Examples 1 to 3> In Examples 1 to 4 and Comparative Example 1, yttria-containing zirconia powder was prepared with a stabilizer yttria (Y2O3) content of 2.9 mass% (corresponding to 1.5 mol%). In Comparative Example 2, the yttria content was set to 5.2 mass% (corresponding to 3.0 mol%), and in Comparative Example 3, the yttria content was set to 9.4 mass% (corresponding to 5.5 mol%). In the case of zirconia powder not containing a stabilizer, it is difficult to obtain a sintered body containing tetragonal zirconia, which is a factor in expressing fracture toughness, even if it is sintered, so in this example, yttria-containing zirconia powder is used. Note that alumina (Al2O3) is contained in Example 3 and Comparative Example 3. Such zirconia powder was uniaxially press molded under a pressure of 10 MPa and cold isostatic pressing (CIP) treatment was performed under a pressure of 196 MPa to obtain a rectangular parallelepiped molded body with a length a (mm), a width b (mm), and a length c (mm). The sizes of each molded body (values of a, b, and c) are shown in the table below.
[0055] A Pt paste was applied to the compact thus obtained so that the interelectrode distance (Le) was 18 mm (Examples 1 to 4 and Comparative Examples 1 and 3) or 15 mm (Comparative Example 2), and then a Pt wire was wound around the Pt-coated portion and connected to the lead wire of a power supply. The compact was then introduced into a sintering furnace, and the temperature inside the furnace was raised at 600°C / h so that the temperature inside the furnace reached the predetermined temperature of 900°C or 1100°C. When the temperature inside the furnace reached the predetermined temperature, an AC electric field was applied to the compact to be sintered, and flash sintering was performed.
[0056] The current density was increased to the holding current density shown in Table 2, and the flash state was maintained for a predetermined time, after which the applied current was turned off, the temperature inside the furnace was lowered to room temperature, and the sintered body was taken out. The part outside the electrode part (including the Pt paste application part) was removed from the taken-out sintered body, and the actual density was measured.
[0057] Table 1 summarizes the powder compositions, compact sizes, and electrode distances of Examples 1 to 4 and Comparative Examples 1 to 3. In Table 1, "wt%" is synonymous with "mass%." Table 2 also summarizes the flash sintering conditions and the evaluation results of the properties of the sintered bodies.
[0058] [Table 1]
[0059] [Table 2]
[0060] As can be seen from these tables, the sample of Comparative Example 1, in which the maximum sample temperature during power increase was as high as 1685°C, exceeding 1650°C, had a relatively low relative density of 96% compared to Examples 1 to 4, and the grain size difference was also large at 40 nm, resulting in a non-uniform sintered body.
[0061] In addition, the sample of Comparative Example 2, which had a high yttria concentration of 5.2 mass%, was sintered under the same conditions as those of Example 2, but had a lower relative density of 92% compared to that of Example 2 and a large particle size difference of 45 nm, resulting in a non-uniform sintered body.
[0062] In addition, in Comparative Example 3, which has an even higher yttria concentration of 9.4 mass % than in Comparative Example 2, the holding current density was 180 mA / mm 2 In this example, an excessive current was passed through the sample so that the sample temperature during holding was 1490° C. When the current during the application of the AC electric field was this high, even if the sample temperature during holding was relatively high, the relative density was low at 97% compared to those in Examples 1 to 4, and the grain size difference was large at 500 nm, resulting in a non-uniform sintered body.
[0063] <Examples 5 and 6> In Examples 5 and 6, the molded bodies were heated in a furnace at 50° C. / h and then held at 1000° C. for 1 hour for pre-sintering, and then flash sintered as sintering samples.
[0064] Table 3 summarizes the powder compositions, compact sizes, and electrode distances of Examples 5 and 6. Table 4 also summarizes the flash sintering conditions and the evaluation results of the properties of the sintered bodies.
[0065] [Table 3]
[0066] [Table 4]
[0067] Comparing Example 5 with Example 1, it can be seen that by performing pre-sintering, even if flash sintering is performed at 900°C, which is a temperature lower than 1100°C, a zirconia sintered body with high relative density (99%) and small particle size difference (35 nm) can be obtained.
[0068] In addition, when Example 6 is compared with Example 3, it is found that the relative density is improved (100%) and the particle size difference is reduced (0 nm) by carrying out preliminary sintering.
[0069] Thus, according to the present disclosure, a high-density and homogeneous zirconia sintered body can be obtained even if the content of the stabilizing element is relatively low compared to the conventional one. Although the mechanism is not necessarily clear, it is believed that the load on the sintered body is reduced by shortening the sintering time compared to the conventional flash sintering method, so that a high-density and homogeneous zirconia sintered body can be obtained with high quality even if the amount of the stabilizing element contained is relatively small.
[0070] As described above, the method for producing a zirconia sintered body according to the present disclosure is a process for heating a zirconia molded body, which is a sample to be sintered, in a sintering furnace, and f The present disclosure includes a heating step in which the zirconia molded body is heated to a predetermined temperature (T ), and a densification step in which, after the heating step, an AC electric field is applied to the zirconia molded body to promote sintering and densification of the molded body by a flash phenomenon. The zirconia molded body contains a stabilizing element at a concentration of 2.0 mass % or more and less than 5.2 mass % in terms of oxide. In the present disclosure, the densification step is performed by applying an AC electric field to the zirconia molded body to promote sintering and densification of the molded body by an oxide flash phenomenon. s ) is carried out under conditions in the range of 900°C or higher and 1650°C or lower. T s =[(T f+273.15) 4 +W / εAσ] 0.25 -273.15 T s and T f Unit:℃ W: Input power (mW) = Applied current (mA) x Applied voltage (V) ε: Emissivity of the sample to be sintered σ: Stephan-Boltzmann constant (5.67×10 -8 Wm -2 K -4 ) A: Surface area of the sample to be sintered where the AC electric field is applied (mm 2 )
[0071] In one embodiment, the predetermined furnace temperature in the temperature increasing step is 600°C or higher and 1200°C or lower.
[0072] Moreover, the application time of the AC electric field in the densification step is preferably less than 5 minutes, and more preferably 3 minutes or less.
[0073] The zirconia sintered body obtained by the method for producing a zirconia sintered body according to the present disclosure is a zirconia sintered body containing a stabilizing element, and the concentration of the stabilizing element in the zirconia sintered body is 2.0 mass% or more and less than 5.2 mass% in terms of oxide, and when the grain size of the sintered body is evaluated in terms of a circle equivalent diameter, the average crystal grain size (d s ) and the average grain size in the inner region, which is deeper than the surface region (d i ) and the particle size difference (d i -d s ) may be less than 40 nm.
[0074] In a preferred embodiment, such a zirconia sintered body has a relative density of 98% or more, as calculated by the following formula. Relative density (%): (measured density ρ / true density ρ0) x 100 Measured density ρ: The ratio of mass measured by mass measurement to volume measured by Archimedes' method (g / cm3 ) True density ρ0: The value calculated by the following formula when the content (mol%) of the oxide of the stabilizing element contained in the sintered body is X ρ0=[124.25(100-X)+225.81X] / 2αβ[150.5(100+X)] Here, α and β have the following values: α=0.5080+0.06980X / (100+X) β=0.5195-0.06180X / (100+X)
[0075] As described above, the stabilizing element is preferably at least one selected from the group consisting of Y, Ca, Mg and lanthanoids. [Industrial Applicability]
[0076] The present disclosure makes it possible to shorten the sintering time compared to the conventional flash sintering method, reduce the environmental load, and produce a high-density and homogeneous zirconia sintered body while reducing the thermal load on the target sample during sintering. In addition, sintering is performed at the actual temperature (effective temperature) of the sintered sample in which densification is progressing due to the flash phenomenon, resulting in a high-density and homogeneous zirconia sintered body of high quality. [Explanation of symbols]
[0077] 10. Sintering target sample 20 Conductor wire (Pt wire) 30 Pt paste 40 Sintering furnace 50 Power supply 60 Thermocouple 100 Zirconia sintered body manufacturing equipment
Claims
1. A process for heating a zirconia compact, which is a sample to be sintered, in a sintering furnace, the furnace temperature (T f a heating step of heating the mixture to a predetermined temperature; and a densification step in which, after the heating step, an AC electric field is applied to the zirconia compact to promote sintering and densification of the compact by a flash phenomenon. The zirconia molded body contains a stabilizing element having a concentration of 2.0% by mass or more and less than 5.2% by mass in terms of oxide, The densification step is performed at an effective temperature (T s The method for producing a zirconia sintered body, wherein the temperature of the sintered body is in the range of 900° C. or more and 1650° C. or less. T s = [(T f +273.15) 4 + W / ε A σ] 0.25 -273.15 T s and T f Unit: ℃ W: Input power (mW) = Applied current (mA) x Applied voltage (V) ε: Emissivity of the sample to be sintered σ: Stephan-Boltzmann constant (5.67×10 -8 Wm -2 K -4 ) A: Surface area of the AC electric field application region of the sample to be sintered (mm 2 )
2. The method for producing a zirconia sintered body according to claim 1, wherein the predetermined furnace temperature in the heating step is 600°C or higher and 1200°C or lower.
3. The method for producing a zirconia sintered body according to claim 1 or 2, wherein the application time of the AC electric field in the densification step is less than 5 minutes.
4. The method for producing a zirconia sintered body according to claim 1 or 2, wherein the frequency of the AC electric field is higher than 10 Hz and not higher than 2000 Hz.
5. The current density when the AC electric field is applied is 0 mA / mm 2 Higher than 100mA / mm 2 The method for producing a zirconia sintered body according to claim 1 or 2, wherein the following is true:
6. The method for producing a zirconia sintered body according to claim 1 or 2, wherein the electric field strength when the AC electric field is applied is higher than 0 V / cm and 200 V / cm or less.
7. The method for producing a zirconia sintered body according to claim 1 or 2, wherein the stabilizing element is at least one selected from the group consisting of Y, Ca, Mg and lanthanoids.
8. The method for producing a zirconia sintered body according to claim 1 or 2, wherein the zirconia sintering sample contains alumina.
9. The method for producing a zirconia sintered body according to claim 8, wherein the alumina content is more than 0 mass% and 1 mass% or less.
10. A zirconia sintered body containing a stabilizing element, The concentration of the stabilizing element in the zirconia sintered body is 2.0% by mass or more and less than 5.2% by mass in terms of oxide, When the grain size of a sintered body is evaluated in terms of the circle equivalent diameter, the average crystal grain size (d s ) and the average crystal grain size (d i ) and the particle size difference (d i -d s ) is less than 40 nm.
11. The zirconia sintered body according to claim 10, wherein the relative density of the sintered body calculated by the following formula is 98% or more. Relative density (%): (actual density ρ / true density ρ 0 ) x 100 Measured density ρ: the ratio of mass measured by mass measurement to volume measured by Archimedes' method (g / cm 3 ) True density ρ 0 : The value calculated by the following formula when the content (mol%) of the oxide of the stabilizing element contained in the sintered body is X ρ 0 =[124.25(100-X)+225.81X] / 2αβ[150.5(100+X)] Here, α and β have the following values: α=0.5080+0.06980X / (100+X) β=0.5195-0.06180X / (100+X)
12. The zirconia sintered body according to claim 10 or 11, wherein the stabilizing element is at least one selected from the group consisting of Y, Ca, Mg and lanthanoids.
Citation Information
Patent Citations
Manufacturing method for sintered body and sintered body
JP2019182689A
Method of producing sintered zirconia
JP2022105852A
